Traditional Chinese Medicine, Qingfei Paidu Decoction and Xuanfei Baidu Decoction, Inhibited Cytokine Production via NF-κB Signaling Pathway in Macrophages: Implications for Coronavirus Disease 2019 (COVID-19) Therapy - Li, Yujia; Li, Bin; Wang, Pan; Wang, Qinghua (Frontiers in Pharmacology, 2021)
Background and Aims: Qingfei Paidu decoction (QPD) and Xuanfei Baidu decoction (XBD) are two typical traditional Chinese medicines with proven efficacy for the treatment of SARS-CoV-2, although the underlying mechanism is not well defined. Blunted immune response and enhanced production of pro-inflammatory cytokines (cytokine storm) are two main features observed in patients infected with SARS-CoV-2. Analysis based on network pharmacology has revealed that both QPD and XBD played an important role in the regulation of host immunity. We therefore investigated the role of QPD and XBD in the modulation of innate immunity in vitro, focusing on the type 1 interferon (IFN) signaling pathway in A549 cells and pro-inflammatory cytokine production in macrophages. Methods: A549 cells were treated with QPD or XBD and the production of endogenous IFNα and IFNβ as well as the expression levels of some interferon-stimulated genes (ISGs) were detected by reverse transcriptase-quantitative PCR (RT-qPCR). Macrophages derived from THP-1 cells were treated with QPD or XBD and their pro-inflammatory cytokine expression levels were measured by RT-qPCR, 6 h post LPS stimulation. In addition, the expression levels of some pro-inflammatory cytokines were further analyzed by ELISA. The effect of QPD and XBD on the NF-κB signaling pathway and the pinocytosis activity of THP-1-derived macrophages were evaluated by Western blot and neutral red uptake assay, respectively. Results: Although QPD and XBD showed very little effect on the type 1 IFN signaling pathway in A549 cells, either QPD or XBD markedly inhibited the production of pro-inflammatory markers including interleukin-6, tumor necrosis factor-α, monocyte chemotactic protein-1, and chemokine ligand 10 in THP-1-derived M1 macrophages. In addition, the phosphorylation of IκBα and NF-κB p65 during the process of macrophage polarization was significantly suppressed following QPD or XBD treatment. QPD and XBD also suppressed the pinocytosis activity of macrophages. Conclusion: QPD and XBD have been shown to have robust anti-inflammatory activities in vitro. Our study demonstrated that both QPD and XBD decreased pro-inflammatory cytokine expression, inhibited the activation of the NF-κB signaling pathway, and blunted pinocytosis activity in THP-1-derived macrophages.